2020
DOI: 10.15252/embr.201949129
|View full text |Cite
|
Sign up to set email alerts
|

IGF 1R regulates retrograde axonal transport of signalling endosomes in motor neurons

Abstract: Signalling endosomes are essential for trafficking of activated ligand–receptor complexes and their distal signalling, ultimately leading to neuronal survival. Although deficits in signalling endosome transport have been linked to neurodegeneration, our understanding of the mechanisms controlling this process remains incomplete. Here, we describe a new modulator of signalling endosome trafficking, the insulin‐like growth factor 1 receptor (IGF1R). We show that IGF1R inhibition increases the velocity of signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 73 publications
5
51
0
Order By: Relevance
“… 67 ) and dynactin, cause peripheral neuropathy 68 , 69 . In addition, activation of IGF1R, a neurotrophic factor receptor found at the NMJ, is involved in regulating signalling endosome dynamics in motor neurons 70 , which may be a common function of similar receptors like TrkB 71 . Furthermore, high levels of phosphorylated IGF1R at NMJs may confer resistance to motor degeneration in ALS mice 72 , suggesting that levels of neurotrophic factors and/or their receptors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“… 67 ) and dynactin, cause peripheral neuropathy 68 , 69 . In addition, activation of IGF1R, a neurotrophic factor receptor found at the NMJ, is involved in regulating signalling endosome dynamics in motor neurons 70 , which may be a common function of similar receptors like TrkB 71 . Furthermore, high levels of phosphorylated IGF1R at NMJs may confer resistance to motor degeneration in ALS mice 72 , suggesting that levels of neurotrophic factors and/or their receptors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…63) and dynactin, cause peripheral neuropathy 64,65 . Additionally, activation of IGF1R, a neurotrophic factor receptor found at the NMJ, is involved in regulating signalling endosome dynamics in motor neurons 66 , which may be a common function of similar receptors like TrkB 67 . Furthermore, high levels of phosphorylated IGF1R at NMJs may confer resistance to motor degeneration in ALS mice 68 , suggesting that levels of neurotrophic factors and/or their receptors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Complementing an array of intravital techniques developed to assess in vivo axonal transport [15], we provide an in-depth, stepwise protocol to image bidirectional axonal transport of multiple cargo types within motor and sensory neurons of the sciatic nerve in live, anesthetized rodents. This technique has been used to confirm that several, but not all, mouse models of neurological disorders display early symptomatic deficits in axonal transport of signaling endosomes [17][18][19][20], indicating that disturbances in the process are not simply a biproduct of neurodegeneration and that impaired transport may play a causative role in only selected neuropathologies. Sciatic nerve exposure and imaging can also be coupled with a battery of transgenic fluorescent reporter strains [31,32] in order to broaden the cargo types that can be imaged, as performed in ALS models [17,33].…”
Section: Applicabilitymentioning
confidence: 99%
“…These probes are internalized at the neuromuscular junction and afferent nerve endings before being retrogradely transported within signaling endosomes toward the cell body of motor and sensory neurons of the sciatic nerve [ 16 ]. We have used this method to show that mutant SOD1 G93A and TDP-43 M337V mice modelling ALS display early deficits in signaling endosome transport in vivo [ 17 , 18 ], which can be rescued in SOD1 G93A mice by p38 MAPK [ 19 ] or IGF1R inhibition [ 20 ]. Indicating that neurodegeneration is not always linked to disturbances in transport, we have shown that endosome trafficking remains unaffected in Fus Δ14/+ ALS mice, spinal and bulbar muscular atrophy mice, and aged wild-type animals [ 18 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation